RAMAN SPECTRA OF POTASSIUM CARBONATE AND BICARBONATE AQUEOUS FLUIDS AT ELEVATED TEMPERATURES AND PRESSURES: COMPARISON WITH THEORETICAL SIMULATIONS - Frantz J.D. (My University, 1998)
One-molal solutions of potassium carbonate and potassium bicarbonate were investigated by Raman spectroscopy from 22° to 550°C and from 1000 to 2000 bar. Experiments were performed in a special hydrothermal pressure vessel fitted with conical diamond windows. Frequencies and half-widths of the vibrational modes were measured for both carbonate and bicarbonate as a function of temperature and pressure. In the case of potassium carbonate solutions, dissolved bicarbonate appeared with its concentration dramatically increasing with increasing temperature and decreasing density. The opposite behavior occurred in the case of potassium bicarbonate: the relative concentration of dissolved carbonate increased relative to total bicarbonate. In addition, at temperatures above 300°C, dissolved aqueous carbon dioxide appeared with its concentration continuing to increase with increasing temperature and decreasing density. Simulations using theoretically-predicted mass action constants were used to compute changes in solution speciation for these solutions as they were subjected to increased temperature and pressure. Results resulting from these predictions matched those discovered in the spectral measurements.
Keywords: POTASSIUM CARBONATE; POTASSIUM BICARBONATE; RAMAN SPECTROSCOPY